Comparison of the effectiveness of amblyopia treatment with eye-patch and binocular Occlu-tab for the same treatment duration - Tomoya Handa; Hansa Thakkar; Minu Ramakrishnan; Kalpit Shah; Vaishali Prajapati; Sania Sayed; Aishwarya Joshi; Yo Ishigaki (Indian Journal of Ophthalmology, 2022)
Purpose: This study aimed to compare the conventional eye patch with Occlu-tab—a binocular open-type amblyopia training device—and evaluate their effectiveness in amblyopia treatment. Methods: In this prospective, multi-center study, 40 patients between ages 3 to 12 years, diagnosed with anisometropic amblyopia (refraction difference of both eyes ≥ 2 D, best-corrected visual acuity [BCVA] of the amblyopic eye ≤ 0.1 [logMAR]) were treated with Occlu-tab or conventional eye patch for 1 h per day thrice a week. We compared the visual acuity of both groups before and after 6, 7, and 8 weeks of amblyopia treatment. One-way repeated-measures analysis of variance and Tukey's test were used to compare the visual acuity of both groups pre- and post-treatment. Results: Both groups had significantly improved visual acuity at 6, 7, and 8 weeks compared to that before treatment (all P < 0.001). The improvement in BCVA of the Occlu-tab group (0.33 ± 0.25) was significantly greater than that of the eye patch group (0.16 ± 0.17) after 8 weeks of treatment (P = 0.02). Conclusion: Amblyopia treatment using binocular open game training with Occlu-tab led to greater improvement in visual acuity than that with a conventional eye patch for the same treatment duration.